PENGARUH SUMBERDAYA MANUSIA, KINERJA DAN BUDAYA KERJA TERHADAP PELAYANAN PUBLIK DI KANTOR DINAS ENERGI DAN SUMBERDAYA MINERAL DAERAH PROVINSI SULAWESI UTARA - LUKAS, YOAS ELLYASAF; KEKENUSA, JHON; PIOH, NOVIE (Sam Ratulangi University, 2019)
As the executor of development and state administrators, the government in this case employees (ASN andTHL) is obliged to protect (to protect the people), serve (to serve the people), and regulate (to regulate thepeople) all of which are